Frontoparietal and default mode network connectivity varies with age and intelligence. (April 2021) - DeSerisy, Mariah; Ramphal, Bruce; Pagliaccio, David; Raffanello, Elizabeth; Tau, Gregory; Marsh, Rachel; Posner, Jonathan; Margolis, Amy E.
Abstract: Background: Anticorrelated resting state connectivity between task-positive and task-negative networks in adults supports flexible shifting between externally focused attention and internal thought. Findings suggest that children show positive correlations between task-positive (frontoparietal; FP) and task-negative (default mode; DMN) networks. FP-DMN connectivity also associates with intellectual functioning across the lifespan. We investigated whether FP-DMN connectivity in healthy children varied with age and intelligence quotient (IQ). Methods: We utilized network-based statistics (NBS) to examine resting state functional connectivity between FP and DMN seeds in N = 133 7−25-year-olds (Mage = 15.80). Linear regression evaluated FP-DMN associations with IQ. Results: We detected NBS subnetworks containing both within- and between-network connections that were inversely associated with age. Four FP-DMN connections showed more negative connectivity between FP (inferior frontal gyrus and precentral gyrus) and DMN regions (frontal medial cortex, precuneus, and frontal pole) among older participants. Frontal pole-precentral gyrus connectivity inversely associated with IQ. Conclusions: FP-DMN connectivity was more anticorrelated at older ages, potentially indicating dynamic network segregation of these circuits from childhood to early adulthood. Youth with more mature (i.e., anticorrelated) FP-DMN connectivity demonstrated higher IQ. Our findings add to the growing body of literature examining neural network development and its association with IQ.